DISTRIBUSI DOSIS PHOTON MENGGUNAKAN TEKNIK 3DCRT DAN IMRT PADA RADIASI WHOLE PELVIC KARSINOMA SERVIKS - Suhartono, Bambang Haris; Setia Budi, Wahyu; Hidayanto, Eko (BERKALA FISIKA, 2014)
Cancer therapy in carcinoma of the cervix performed with external radiotherapy modalities box beam photon field and 3-Dimension Conformal Radiotherapy (3DCRT) and Intensity Modulation Radiation Therapy (IMRT). IMRT compared with 3DCRT technique on whole-pelvic radiation cervical carcinoma by analyzing the distribution of dose or planning the target volume (PTV) coverage through homogeneity index (HI) and Conformity Index (CI) as well as the organ risk (OAR).This study uses 44 patient data in Installation Radiotherapy Hospital Dr. Soetomo with radiation planning 25x2 Gy of whole pelvic radiation with two planning techniques using the box 3DCRT and IMRT techniques on the angle of rotation 0, 180, 270, and 90 degrees, and then compare the Dose Volume Histograms (DVH) coverage on PTV, rectum and bladder. CI values ​​for the 3DCRT technique (0.812 ± 0.067) and the IMRT technique was (0.799 ± 0.088) values ​​obtained by t test (p = 0.405), whereas for the HI value for 3DCRT technique (1.075 ± 0.079) and the IMRT technique for (1.075 ± 0.079) with values ​​(p = 0.219). Both CI and HI values ​​are not significant. Comparison of percentage of dose on the risk of organ rectum with 3DCRT and IMRT techniques consecutive (80.56 ± 11.21) and (68.14 ± 8.01) with the value (p = 0.00), whereas for bladder organ 3DCRT techniques and consecutive IMRT (80.52 ± 9.22) and (71.94 ± 7.65) with the value (p = 0.00). There is significant value in the percentage of the dose in the rectum and bladder Keywords: Whole pelvic, IMRT, 3DCRT, HI, CI